Critical Role of Plasmacytoid Dendritic Cells in Regulating Gene Expression and Innate Immune Responses to Human Rhinovirus-16 - Xi, Yang; Troy, Niamh M.; Anderson, Denise; Pena, Olga M.; Lynch, Jason P.; Phipps, Simon; Bosco, Anthony; Upham, John W. (Frontiers in Immunology, 2017)
Though human rhinoviruses (HRV) are usually innocuous viruses, they can trigger serious consequences in certain individuals, especially in the setting of impaired interferon synthesis. Plasmacytoid dendritic cells (pDC) are key IFN producing cells, though we know little about the role of pDC in HRV-induced immune responses. Herein we used gene expression microarrays to examine HRV-activated peripheral blood mononuclear cells (PBMC) from healthy people, in combination with pDC depletion, to assess whether observed gene expression patterns were pDC dependent. As expected, pDC depletion led to a major reduction in IFN-α release. This was associated with profound differences in gene expression between intact PBMC and pDC depleted PBMC, and major changes in upstream regulators: 70-80% of the HRV activated genes appeared to be pDC dependent. RT-PCR confirmed key changes in gene expression, in which the following selected genes were shown to be highly pDC dependent: the transcription factor IRF7, both IL-27 chains (IL-27p28 and EBI3), the alpha chain of the IL-15 receptor (IL-15RA) and the IFN related gene IFI27. HRV-induced IL-6, IFN-γ and IL-27 protein synthesis were also highly pDC dependent. Supplementing pDC-depleted cultures with either recombinant IL-15, IFN-γ, IL-27 or IL-6 was able to restore the IFN-α response, thereby compensating for the absence of pDC. Though pDC comprise only a minority population of migratory leukocytes, our findings highlight the profound extent to which these cells contribute to the immune response to HRV.